Efficient sensor data collection with dynamic traffic patterns - Zhao, Wenbo (2014)
In a typical monitoring application, sensor nodes periodically sample the physical world and their acquired data are continuously collected by a base station. In continuous sensor data collection, due to the energy conservation concerns or the nature of the sensor applications, not all data are reported to the base station at each sampling interval. Decisions of what data to report are driven by data itself and can only be made after the data are acquired by sensor nodes. As a result, the traffic pattern in the network often changes over time in an unpredictable manner. This thesis studies the construction of TDMA schedules and routing structures to efficiently handle dynamic traffic patterns in continuous sensor data collection.